Validation and Factor Analysis of the Obsessive Compulsive Drinking Scale (OCDS) in the Chinese Population - Wang, Hongxuan; Lan, Lihuan; Lan, Xiaochang; Chen, Peiyun; Liu, Gaoxin; Rong, Xiaoming; Liu, Lei; Kang, Chuan-Yi; Yang, Jianzhong; Guan, Yan-Zhong; Zhu, Xiao-Feng; Hu, Jian; et al. (Frontiers in Psychiatry, 2021)
Obsessive Compulsive Drinking Scale (OCDS) was established and introduced to measure the craving for alcohol and the severity of alcohol dependence. However, Chinese version of OCDS is still unavailable and has not been validated in Chinese population. We tended to translate and validate the OCDS in Chinese. We translated original OCDS into Chinese through bi-direction translations and tested the reliability and validity. We found that Chinese OCDS had high internal consistency and good test-retest reliability. The Chinese OCDS also presented good internal structure to reflect the severity of alcohol dependence. The Chinese OCDS could be used in the clinical studies and research among Chinese population.